Answer:
Option D: f(a) = 2a²+2a-4 is the correct answer.
Explanation:
Given that:
f(x)=2x²+2x-4
We will check the function at the given value;
A. f(0)
Putting x=0 in given function
f(0) = 2(0)²+2(0) - 4
f(0) = 0+0-4
f(0) = -4
B. f(-1)
Putting x=-1
f(-1) = 2(-1)²+2(-1)-4
f(-1) = 2(1) -2-4
f(-1) = 2-6
f(-1) = -4
C. f(b+1) = 2b²+6b-4
Putting x=b+1
f(b+1) = 2(b+1)²+2(b+1)-4
f(b+1) = 2(b²+2b+1)+2b+2-4
f(b+1) = 2b²+4b+2+2b+2-4
f(b+1) = 2b²+6b
D. f(a) = 2a²+2a-4
Putting x=a
f(a) = 2(a)²+2(a)-4
f(a) = 2a²+2a-4
Hence,
Option D: f(a) = 2a²+2a-4 is the correct answer.